Nutrition Education for Adolescents: Building Healthy Eating Habits at Growing Age - Fuad Ajrul Mukhdi (Journal Nutrizione, 2024)
This study explores the effectiveness of nutrition education in building healthy eating habits among adolescents, which is a crucial age for growth and development. Although adolescents have basic knowledge about the importance of nutrition, such as the benefits of vitamins and minerals, the information they receive is often not in-depth or practical enough to be applied in daily habits. This study identifies that current nutrition education programs are often less interactive and not always relevant to the context of adolescent life. Through qualitative methods, this study reveals the challenges faced by adolescents in implementing healthy eating habits, such as peer influence and limited access to healthy food. The findings suggest that a more holistic approach is needed to address these barriers. Strategies that involve more practical and participatory educational methods, as well as support from families and communities, have proven effective in increasing understanding and application of nutrition principles. The results of the study explain that educational programs involving practical activities, educational games, and family and community participation can help adolescents make healthy food decisions and support their growth and overall health.